Reduction of Aggressive Behavior Levels in Adolescent Adolescents with Emotional Regulation Therapy - Endang Mei Yunalia; Idola Perdana Sulistyoning Suharto (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Aggressive behavior is a behavior disorder especially if it occurs repeatedly and persists for at least 6 months. Aggressive behavior occurs because adolescent express negative emotions in an inappropriate way. The solution to help adolescent to be able to express emotions appropriately is with emotion regulation therapy. The purpose of this study was to determine the effectiveness of emotional regulation therapy on the level of aggressive behavior in young men. This research is a Quasy experimental study using one group pre-post test design with control design. The population in this study was all young men with "X" high school. A sample of 48 respondents were selected using purposive sampling which was divided into 24 respondents in the intervention group and 24 respondents in the control group. The statistical test used is the Wilcoxon Signed Ranks Test. Statistical test results show that p = 0,000 (p-value <0.05), which means that there is an influence of emotional regulation therapy on aggressive behavior in young men with aggressive behavior so that it proves a decrease in the level of aggressive behavior in young men. Based on the results of this study it can be seen that emotional regulation therapy is one way that can be given to adolescents to reduce the level of aggressive behavior in adolescents through efforts to control negative emotions.